THE RELATIONSHIP BETWEEN INDIVIDUAL CHARACTERISTICS AND OCCUPATIONAL FACTORS TO LOW BACK PAIN COMPLAINTS AMONG LPG AGENT WORKERS AT MANGGARAI SUBDISTRICT JAKARTA IN 2020 - Oktavia, Salma Devita (Journal of Public Health Research and Community Health Development, 2022)
ABSTRACT Based on observations of most of the workers at the LPG agent at Kelurahan Manggarai deploying gas cylinders manually for (± 8 hours) and the frequency of activities undertaken by workers is very high, based on interviews conducted by researchers found that most workers experience pain in the lower back. This can increase tension in the muscles and cause disability. This study aimed to determine the relationship between individual characteristics and occupational factors with complaints of low back pain in LPG agent workers at Kelurahan Manggarai Jakarta in 2020. This research was quantitative by using a cross-sectional design. The sampling technique was by total sampling where the number of samples was 52 people. Data were analyzed using the Chi-Square test. Workers' body positions were observed by adjusting the OWAS observation assessment sheet. The results of the analysis found that age, BMI, smoking habits, manual material handling and years of work have a significant relationship with LBP complaints (p-value <0.05), whereas physical activity does not have a significant relationship with LBP complaints (p-values >0.05). The company should create a two-wheeled hand truck based on worker anthropometry to minimize LBP complaints. ABSTRAK Berdasarkan hasil observasi sebagian besar pekerja pada agen LPG Kelurahan Manggarai Jakarta mengerahkan tabung gas secara manual selama kurang lebih 8 jam serta frekuensi aktivitas yang dilakukan pekerja sangat tinggi. Berdasarkan hasil wawancara yang dilakukan peneliti ditemukan sebagian besar pekerja mengalami LBP. Hal ini dapat meningkatkan ketegangan pada otot dan menimbulkan kecacatan. Penelitian ini bertujuan mengetahui hubungan karakteristik individu dan faktor pekerjaan dengan keluhan low back pain pada pekerja di agen LPG Kelurahan Manggarai Jakarta tahun 2020. Sebanyak 52 orang dilibatkan dalam penelitian ini dengan menggunakan teknik total sampling. Penelitian ini bersifat kuantitatif dengan menggunakan desain cross-sectional. Data dianalisis menggunakan uji Chi-Square. Posisi tubuh pekerja diamati dengan menyesuaikan lembar penilaian observasi OWAS. Hasil analisis menunjukan bahwa variabel usia, IMT, kebiasaan merokok, manual material handling, dan masa kerja memiliki hubungan yang bermakna dengan keluhan LBP (nilai-p <0,05), sedangkan aktivitas fisik tidak memiliki hubungan yang bermakna dengan keluhan LBP (nilai-p >0,05). Sebaiknya, perusahaan menciptakan hand truck dua roda yang dibuat berdasarkan antropometri pekerja agar meminimalisasi terjadinya keluhan LBP.